Effects of grain size on the structural, electrical, magnetic and magnetotransport properties of polycrystalline Laₒ.₆₇Srₒ.₃₃MnO₃ synthesized via different methods - Chin, Hui Wei (2014)
In recent decades, the extrinsic magnetoresistance (MR) has been widely studied due to their potential application at low field. Extrinsic MR is caused by spin polarized tunneling (SPT) and spin dependent scattering (SDS) between grains, which originates from the grain size variation and grain boundary effect. It can be enhanced by adjusting their extrinsic characteristic, for example by adding composite and size reduction. In this work, the focus is on the effect of grain size variation on La0.67Sr0.33MnO3 (LSMO) samples which were synthesized through solid state (SS), co-precipitation (CP) and sol-gel (SG) methods. The influence of different sintering temperature (different range of grain sizes) towards structural, magnetic, electrical and magnetotransport properties was studied, from 600˚C up until 1200 ˚C. Different sintering temperature is required to obtain pure single phase compound when different synthesis methods are used. CP and SS samples show pure La0.67Sr0.33MnO3 (ICSD code: 156020) phase with hexagonal structure (R3c) at 1100 ˚C and 1200 ˚C, respectively. However, SG samples gave single phase compound at lower sintering temperature (600 ˚C). The increase of sintering temperature promotes significant grain growth and microstructure densification, thus grain size increases. Through SEM analysis, the smaller grain (around 42.7-194.4 nm) can be found in SG sample which was lower than 200 nm even when sintered at 1200 ºC. Magnetization decreases with grain size. Curie temperature (Tc) of SS12, CP12 and SG12 were 373 K, 375 K and 358 K, respectively. Decrease of Tc and magnetization were not only grain size (effective grain boundaries) dependent but also grain size distribution and formation. The resistivity is found to be higher for LSMO SG samples having nanograin size with higher effective grain boundaries. Thus, metal- insulator transition (Tp) shifted to lower temperature. Nanosized particles that consist of higher effective grain boundaries can enhance the magnetoresistance (MR) value but decreases of magnetization. The highest extrinsic MR % was given by the smallest grain size (42.7 nm) in LSMO SG6 with -9.16 % in 10 kG at 80 K. It also contributes to significantly high CMR value (-19.6 %) in 10 kG at 80 K. Overall, the results show that the structure, magnetic and magnetoresistive properties are strongly dependent on their grain size distribution and formation, which is affected by synthesis methods and sintering effects. As the grain size becomes smaller, resistivity and magnetoresistence increase however magnetization decreases. Tp also shifted to lower temperature, extrinsic MR is more dominant. Vice versa, larger grain size shows lower resistivity, higher magnetization and intrinsic MR is more dominant.